Non-enzymatic hydrogen peroxide detection on a novel nanohybrid composite of chitosan and grafted graphene oxide - Nasir, Amara; Khalid, Sadia; Mazare, Anca Valentina; Yasin, Tariq (Materials Research Bulletin, 2023)
Hydrogen peroxide (H2O2) is a significant constituent of several biological and industrial processes; however, as it is malignant to human health, the ability to detect its presence is indispensable. From the various H2O2 detection methods, enzyme-free electrochemical detection method is thriving in research, as it is economical, easy-to-use, stable, and provides repeatable platforms. Herein, we report on a metal-free, novel, biopolymer-based low-cost, stable, and easy-to-operate, conducting nanohybrid composite for the non-enzymatic detection of H2O2. This nanohybrid composite consists of a novel crosslinked chitosan (CS) and polyaniline (PANI) grafted graphene oxide (GO) (GOP) composite. In the first step, a gamma-irradiated GO (γGO) substrate is used for the in-situ graft polymerization of aniline, and following the grafted nanohybrid was incorporated in a CS matrix and crosslinked with tetraethylorthosilicate (TEOS) to form CS and GO composites. The sensor, fabricated by coating the newly prepared composite on a glassy carbon electrode, was tested for hydrogen peroxide detection in an alkaline solution, showing a low detection limit of 17.3 μM, a linear range up to 200 μM, and a sensitivity of 0.77 μA μM−1 cm−2. These notable results and comparable performance with the literature suggest that the electrochemical biosensor exhibit promising potential for a wide range of H2O2 detection.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Chitosan; Graphene oxide; Hydrogen peroxide; Polyaniline; Sensor